INCLUSIVE EDUCATION IN THE CONDITIONS OF THE MODERN SCHOOL - Vasilyeva, O.M.; Mukhamedzyanova, R.N. (Publisher of Kostanay Regional University named after Akhmet Baitursynov, 2022)
Nowadays, one of the fundamental principles in obtaining education is the principles of the priority of the student, the humanization of education.The current direction of the reform of the education system in Kazakhstan is the so-called «inclusive education».Inclusive education is the provision of equal access to education for all students, taking into account the diversity of special educational needs and individual opportunities. This approach allows us to call «special» any child who is somehow different from the accepted norm. Thus, inclusion is designed to improve the quality of education, upbringing and socialization of all children.
Keywords: inclusive education; children with special educational needs; individual approach